Cobweb Christmas - Climo, Shirley; Manning, Jane K. ([New York] : HarperCollins, 2001)
An old woman in long-ago Germany cleans her house and decorates her Christmas tree, hoping that this year she will witness some special Christmas Eve magic.
School Library Journal
3.9
K-3
Keywords: Christmas -- Fiction; Christmas trees -- Fiction; Magic -- Fiction; Spider webs -- Fiction; Germany -- Fiction; Christmas -- Fiction; Christmas trees -- Fiction; Magic -- Fiction; Spider webs -- Fiction; Germany -- Fiction